Analyzing Consumer Preferences For Mie Gacoan Product Attributes Through Conjoint Analysis In Surabaya - Grecia Pratidina; Jariyah Jariah; Ratna Yulistiani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study aimed to analyze consumer preferences toward Mie Gacoan product attributes in Surabaya using conjoint analysis. The research employed a survey method with 100 respondents selected through non-probability sampling. The attributes examined included noodle variants, menu completeness, payment method, and ordering type. The results showed that noodle variant was the most important attribute (42.42%), followed by menu completeness (28.15%), ordering type (17.83%), and payment method (11.60%). The highest utility values were found for Mie Gacoan's sweet-spicy flavour, the complete bundling package, dine-in service, and the cashless payment method. These findings indicate that product variety and service convenience significantly influence consumer purchasing decisions. The model demonstrated good predictive accuracy (p = 0.000), confirming the reliability of conjoint analysis in explaining consumer preferences. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 17: Partnerships for the Goals